Selected Topics in Midwifery Care - Polona Mivšek, Ana (IntechOpen, 2019)
Midwifery across the globe faces different issues. In some countries the autonomy of the profession is a tradition, while in some societies midwives struggle to practice autonomously the basic competencies. In one part of the world the medicalisation of childbirth is the main issue, preventing the natural processes of pregnancy and childbirth to flow at their own pace, while in other parts of the world midwives struggle with lack of resources to provide safe midwifery care. The authors of this book practice midwifery in different cultures and within different social contexts. They have to deal with different obstacles and seek solutions to diverse problems. With their contributions, they offer an insight into their thinking, their dilemmas, and the problems of midwifery practices in their countries. However, despite different backgrounds, they all have in common a uniform goal - a wish to offer women optimal midwifery care and to improve midwifery services.